Bioleaching for Copper Extraction of Marginal Ores from the Brazilian Amazon Region - Dryelle Nazaré Oliveira do Nascimento; Adriano Reis Lucheta; Maurício César Palmieri; Andre Luiz Vilaça do Carmo; Patricia Magalhães Pereira Silva; Rafael Vicente de Pádua Ferreira; Eduardo Junca; Felipe Fardin Grillo; Joner Oliveira Alves (Metals, 2019)
The use of biotechnology to explore low-grade ore deposits and mining tailings is one of the most promising alternatives to reduce environmental impacts and costs of copper extraction. However, such technology still depends on improvements to be fully applied in Brazil under industrial scale. In this way, the bioleaching, by Acidithiobacillus ferrooxidans, in columns and stirred reactors were evaluated regarding to copper extraction of a mineral sulfide and a weathered ore from the Brazilian Amazon region. Samples (granulometry of 2.0/4.75 mm) were characterized by X-ray diffraction (XRD), energy dispersive X-ray fluorescence (EDXRF) spectrometry and scanning electrons microscopy (SEM). The pH and Oxidation-reduction potential (Eh) were daily monitored and leachate samples were collected for copper extraction determination by EDXRF. After 47 days, the columns bioleaching efficiency was 1% (1298 mg Cu·L−1) and 0.95% (985 mg Cu·L−1) for 2.00/4.75 mm sulfide ore, respectively, whereas the stirred reactors bioleaching resulted in 4% (348 mg Cu·L−1) for the mineral sulfide and 47% (295.5 mg Cu·L−1) for the weathered ore.